Aspek Hukum Perseroan Yang Tidak Melaksanakan Rapat Umum Pemegang Saham (Studi Kasus PT. Pitala Gunawan Raya) - Aprilia Ruhil Nuha; Nurul Istianah; Sumriyah Sumriyah (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
A Limited Liability Company is a form of business that has been regulated in the Limited Liability Company Law which has one important organ, namely the annual general meeting of shareholders. RUPS has a very important role in making strategic decisions, overseeing company performance, and maintaining transparency and accountability. Therefore, the arrangement of RUPS as an important organ in the company. The method used is normative legal research using statute approach and case approach. The legal consequences of companies not holding RUPS are in the form of sanctions which are not listed in Law Number 40 of 2007 Concerning PT so that the government should pay more attention to the importance of RUPS and be able to see this legal loophole to be corrected so that the RUPS can maximize its function for the benefit of the company as well as for the government as a reference for economic growth.